Hypoglycaemia associated with anorexia nervosa. Issue 787 (May 1991) - Fonseca, V.; Ball, S.; Marks, V.; Havard, C. W.
Abstract : A 41 year old woman with severe emaciation due to longstanding anorexia nervosa presented with recurrent hypoglycaemia. During an episode of hypoglycaemia, serum insulin and C peptide were undetectable and plasma beta hydroxybutyrate, free fatty acids and lactate were inappropriately low. Response to intravenous glucagon was poor. Muscle enzymes were grossly elevated until she gained weight. Hypoglycaemia was abolished by weight gain.